2017
DOI: 10.15171/joddd.2017.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of efficacy of subgingivally delivered 1.2% Atorvastatin and 1.2% Simvastatin in the treatment of intrabony defects in chronic periodontitis: a randomized controlled trial

Abstract: Background. Statins are the recently evolved agents that aid in periodontal regeneration and ultimately in attaining periodontal health. Atorvastatin (ATV) and Simvastatin (SMV) are specific competitive inhibitors of 3-hydroxy-2-methyl-glutaryl coenzyme A reductase. The current study was conducted to compare the effectiveness of 1.2% ATV and 1.2% SMV, in addition to scaling and root planing (SRP), in the treatment of intrabony defects in subjects with chronic periodontitis.Methods. Ninety-six individuals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 27 publications
3
21
0
Order By: Relevance
“…Additionally, test site showed a significant reduction in all periodontal parameters (GI, PI, PPD, BOP, CAL) versus control group. These results came in agreement with Martande el al 35 , and sinjab et al; 56 they found that there was more improvement in clinical parameters (PI, PPD, CAL) of test group after locally application of statins as adjunctive to mechanical SRP than control group. Additionally, Rosenberg et al 57 reported that one month using of 2% ATV dentifrice for periodontitis patients, showed greater significant reduction in BOP and GI.…”
Section: Discussion:-supporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, test site showed a significant reduction in all periodontal parameters (GI, PI, PPD, BOP, CAL) versus control group. These results came in agreement with Martande el al 35 , and sinjab et al; 56 they found that there was more improvement in clinical parameters (PI, PPD, CAL) of test group after locally application of statins as adjunctive to mechanical SRP than control group. Additionally, Rosenberg et al 57 reported that one month using of 2% ATV dentifrice for periodontitis patients, showed greater significant reduction in BOP and GI.…”
Section: Discussion:-supporting
confidence: 89%
“…Periodontitis is a multi-factorial disease, resulting in the destruction of periodontal tissues, bone resorption and tooth loss. 35 Non-surgical periodontal therapy in moderate periodontitis is an effective treatment, 36 where local drug delivery is one of the best adjunctives. 37 ATV inhibits the secretion of cytokines in chronic inflammatory diseases.…”
Section: Discussion:-mentioning
confidence: 99%
“…Only 4 studies compared the outcomes obtained with more than one statin; however, contradictory results were observed. For instance, one study did not show any significant difference between atorvastatin and simvastatin [ 100 ], whereas better results were obtained with atorvastatin in another study [ 101 ]. Nevertheless, two studies highlighted greater efficacy with rosuvastatin in comparison with atorvastatin [ 20 , 102 ].…”
Section: Resultsmentioning
confidence: 99%
“…Seven trials employed allocation concealment [3135, 37, 38]. All studies reported whether participants or study personnel were blinded, and three studies [30, 40, 42] did not report whether these groups were blinded to outcome assessment. After considering such little incomplete outcome data, reporting bias and other bias domains, all studies had a low risk of bias.…”
Section: Resultsmentioning
confidence: 99%